The In Vivo Evaluation on Total Components from Extract of Aconitum Based on a New Analytic Method of Area under Absorbance-Wavelength Curve - Miaomiao Yang; Huasong Wu; Xiaodong Li (Journal of Spectroscopy)
Objective. To study oral pharmacokinetics of Aconitum extract in randomized Sprague-Dawley (SD) rats and observe the profile change in vivo between plasma concentration and time with an aim to disclose relevant delivery rule for total components from Aconitum extract and finally to evaluate the research of Aconitum sustained-release preparation. Methods. Randomized rats were administered orally with the single and multiple dose of Aconitum extract based on the clinical use of Aconitum injection. Blood samples were collected at predetermined interval time from an eye of rats. The concentration of total components in those samples was determined by a new analytic method of area under absorbance-wavelength curve, the data were analyzed by Drug and Statistics software, and then the pharmacokinetic parameters and compartment model were acquired and compared, respectively. Results. The pharmacokinetic parameters of single and multiple doses were similar, and both of them showed characteristics of the one-compartment model. Cav, DF, and AUCss were (2.075 ± 0.282) µg/ml, (2.405 ± 0.175), and (24.901 ± 0.422) µg/ml/h, respectively. However, the concentrations of total components in the fifth and sixth day were 0.32 and 0.44 µg/ml, which were lower than the value of Cav. Conclusion. The method of AUAWC is feasible for the pharmacokinetics study in vivo analysis on total components of Aconitum with good sensitivity, specificity, and repeatability. The results demonstrated that both absorption and elimination of total components from Aconitum extract in rats were rapid and pharmacokinetic behavior was consistent at the level of single and multiple doses, which confirms that Aconitum injection is available to transform the oral sustained-release preparation. This will bring a good instruction to the research of sustained-release preparation of traditional Chinese medicine (TCM), which still lacks of an evaluation method available for total components in vivo analysis.